Clinical outcomes of left ventricular unloading with microaxial flow pump Impella during venoarterial extracorporeal membrane oxygenation (VA-ECMO): a systematic review and updated meta-analysis. (3rd October 2022) - Cappannoli, L; Galli, M; Zito, A; Restivo, A; Princi, G; Leone, A M; Vergallo, R; Aurigemma, C; Romagnoli, E; Aspromonte, N; Burzotta, F; Trani, C; et al.
Abstract: Background: Whether the addition of percutaneous microaxial flow pump Impella to venoarterial extracorporeal membrane oxygenation (VA-ECMO) as left ventricle unloading strategy is effective in improving outcomes compared to VA-ECMO alone is still to be proved. Purpose: Aim of this systematic review and meta-analysis was to assess whether patients with refractory cardiogenic shock treated with IMPELLA in addition to VA-ECMO (ECMELLA) versus ECMO alone may benefit a reduction in early mortality and to assess whether this strategy may result in an increased rate of complications. Methods: For this systematic review and meta-analysis, from Dec 2021 to Jan 2022, we searched Scopus, MEDLINE (with PubMed interface) and the Cochrane Central Register of Controlled Trials for randomised controlled trials and observational studies published in any language comparing the use of ECMELLA versus ECMO alone in patients with acute refractory CS (with or without cardiac arrest). Two independent investigators screened titles and abstracts for eligibility, extracted the data, and assessed risk of bias. Risk ratios (RRs) and 95% CIs were calculated with random-effects or fixed-effect models according to the estimated heterogeneity among studies assessed by the I 2 index. Primary efficacy endpoint was trial-defined early mortality (in hospital or 30-day mortality). Safety endpoints were major bleeding, the need for renal replacement therapy, hemolysis, severe infections/sepsis and limb ischemia. This study is registered with PROSPERO (CRD42022292517). Results: 2061 potentially relevant articles were screened. Our analysis included six retrospective studies with data for 1457 patients. Compared with ECMO alone, ECMELLA was associated with a non-significant reduction in early mortality (RR 0.87, 95% CI 0.72–1.06, p=0.17; Figure 1) and in a significant increase of major bleeding (RR 1.45, 95% CI 1.10–1.91, p=0.009), need for renal replacement therapy (RR 1.70, 95% CI 1.16–2.48, p=0.0008), hemolysis (RR 2.22, 95% CI 1.39–3.56, p=0.005) and limb ischemia (RR 1.61, 95% CI 1.20–2.16, p=0.001). No significant differences were observed in the incidence of severe infections/sepsis between the two groups (RR 1.23, 95% CI 0.97–1.58, p=0.09). (Figure 2) Conclusions: The results of this meta-analysis showed that ECMELLA compared to ECMO alone did not significantly reduce early mortality and that, conversely, it resulted in a significantly increased risk of several complication (major bleeding, hemolysis, limb ischemia and renal replacement therapy). This study highlights that, if the benefit of left ventricle unloading with Impella during ECMO in CS shock is uncertain and probably limited to only selected patients, it surely increases the risk of some complications, therefore caution is needed in choosing such a strategy. Funding Acknowledgement: Type of funding sources: None.